(untitled) (Książnica Śląska, 2025)
The author analyzes the successive stages of the development of bibliography, starting from traditional printed versions, through onlindatabases, to digital libraries that provide not only bibliographic descriptions, but also the content of digitized documents. In this article is described also the work of the Municipal Public Library Hugo Kołłątaj in Dąbrowa Górnicza in the field of developing of a regional bibliography.